READING POVERTY IN MODERNIST LITERATURE: RIFFATERRIAN SEMIOTIC ANALYSIS ON T.S ELIOT'S MORNING AT THE WINDOW - Nestiani Hutami; Diaz Adrian (Lakon : Jurnal Kajian Sastra dan Budaya, 2021)
Abstract: The idea of poverty as the theme has been recurrently used in literature. However, it is rarely come across in Modernist Literature. Accordingly, this study examines poverty as the theme, which is also the main issue in a poem written by T.S. Eliot entitled Morning at the Window. To dive deep into the main issue of the poem, it uses a close-reading method. It focuses on how the text of the poem represents the main issue in which the poem tries to convey. To come into the results of the study, three aspects from Semiotics of Poetry by Michael Riffaterre are used, which are unsustainable expressions, heuristic and hermeneutic reading, and matrix. Analyzing these three aspects, the results show that the representation of poverty as the main issue is evidently stated. The diction in the poem successfully creates the images and set the tone that correlates with poverty.